Aspects of Corporate Finance: Inter-firm Lending : Explorations from a Modern European Perspective - Michael Moss (Institut de la gestion publique et du développement économique, 2019)
The papers published in this book were initially prepared for the conference held at the Ministère de l'Économie et des Finances on the 9th and 10th of March, 2017 (Inter-firm credits in Europe 1880‑2010), organized by Michel Lescure in the context of the work of the IGPDE (Institut de la Gestion Publique et du Développement Économique) and of the CHEFF (Comité pour l'Histoire Économique et Financière de la France). The conference and the book have been financed by the IGPDE, the Crédit Agricole, the Société Générale, the IDHE.S Nanterre (Institutions et Dynamiques Historiques de l'Économie et des Sociétés, UMR-CNRS 8533) and the Doctoral School of EOS (Économie-Organisation-Société) of the University Paris-Nanterre. We would like to thank these institutions. The translation of communications by non French-speaking academics was produced by the translation centre of the Economic and Financial Ministries.